2014
DOI: 10.2967/jnumed.114.142083
|View full text |Cite
|
Sign up to set email alerts
|

Imaging DNA Damage Allows Detection of Preneoplasia in the BALB-neuT Model of Breast Cancer

Abstract: A prominent feature of many human cancers is oncogene-driven activation of the DNA damage response (DDR) during early tumorigenesis. It has been shown previously that noninvasive imaging of the phosphorylated histone H2A variant H2AX, γH2AX, a DNA damage signaling protein, is possible using 111 In-labeled anti-γH2AX antibody conjugated to the cell-penetrating peptide transactivator of transcription (TAT). The purpose of this study was to investigate whether 111 Inanti-γH2AX-TAT detects the DDR during mammary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…High concentrations of unlabelled anti-γH2AX-TAT slow down γH2AX foci formation, but have no effect on the resolution of DSBs, as shown by the neutral comet assay (data not shown). We previously showed that 111 In-anti-γH2AX-TAT, labelled with low amounts of 111 In necessary for imaging (<1 MBq/μg), similar to 89 Zr-anti-γH2AX-TAT, also does not affect DSB repair in vitro [11] or cause tumour growth delay in vivo [12]. In this manuscript, we show that this is also the case for the 89 Zr-labelled version, even though the spectrum of emitted particles includes more energetic gamma rays and a beta particle as well as low-energy electrons.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…High concentrations of unlabelled anti-γH2AX-TAT slow down γH2AX foci formation, but have no effect on the resolution of DSBs, as shown by the neutral comet assay (data not shown). We previously showed that 111 In-anti-γH2AX-TAT, labelled with low amounts of 111 In necessary for imaging (<1 MBq/μg), similar to 89 Zr-anti-γH2AX-TAT, also does not affect DSB repair in vitro [11] or cause tumour growth delay in vivo [12]. In this manuscript, we show that this is also the case for the 89 Zr-labelled version, even though the spectrum of emitted particles includes more energetic gamma rays and a beta particle as well as low-energy electrons.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, applications of DNA damage imaging could be envisioned in early detection of tumours, which had been anticipated nearly a decade ago [8]. We have used the DNA damage repair response to oncogenic stress in a mmtv-driven neuT-overexpressing mouse model of breast cancer [12]. Furthermore, DNA damage imaging could aid tumour diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibodies to gH2AX labeled with fluorescent probes are commonly used for laboratory assays of cell death. 111 In-anti-gH2AX-TAT immunoconjugate was used as a SPECT probe for detecting DNA damage in mice during mammary oncogenesis and showed changes before MR imaging (66). 89 Zr-anti-gH2AX-TAT immunoconjugates have also shown promising results in a preclinical breast cancer model with 8-fold-higher uptake in irradiated gH2AX cells than nonirradiated controls (67).…”
Section: Dna Damagementioning
confidence: 99%